New distributional and ecological data of Ochthebius (Gymnochthebius) francki Bruch, 1915 (Coleoptera, Hydraenidae) with a key to the Argentinean species - Macchia, Gabriel A. (2023)
This paper presents new distributional data for Ochthebius (Gymnochthebius) francki (Bruch, 1915), describes the environments and water bodies where it occurs. In addition, it provides a key to the nine Ochthebius (Gymnochthebius) species in Argentina and includes an updated distribution map.